EFEITOS DOS EXERCÍCIOS DE CADEIA CINÉTICA FECHADA NA PREVENÇÃO E TRATAMENTO DA CONDROMALÁCIA PATELAR (REMUNOM, 2025)
Chondromalacia patella is a pathology that is known to cause damage to the patellar cartilage and lead to patellofemoral pain syndrome. This pathology affects around 39.2% of the general population and especially patients aged between 30 and 40 years.The objective of this study was to carry out a literature review on the effects of using closed kinetic chain strength training in cases of patellar chondromalacia.The methodology used is a literature review, carrying out research in the following databases: PUBMED, SCIELO, GOOGLE ACADÊMICO and LILACS.It was concluded that closed kinetic chain exercises are recommended in cases of patellar chondromalacia as they do not cause damage to the knee joint.